A hybrid approach to the valuation of climate change effects on ecosystem services: evidence from the European forests - Helen Ding; Silvia Silvestri; Aline Chiabai; Paulo A. L. D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2010)
In this paper we present a systematic attempt to assess economic value of climate change impact on forest ecosystems and human welfare. In the present study, climate change impacts are downscaled to the different European countries, which in turn constitute the elements of our analysis. First, we anchor the valuation exercise in the Millennium Ecosystem Assessment (MEA) Approach and therefore the link between the different forest ecosystem goods and services, including provisioning, regulating and cultural services, human well-being and climate change. Second, climate change is operationalized by exploring the different storylines developed by the International Panel on Climate Change (IPCC) and applied, downscaled, for each of the European countries under consideration. Third, and bearing in mind the different nature of the benefits provided by the different types of forest ecosystems under examination, we shall explore different economic valuation methodologies so as to shed light on the magnitude of the involved welfare changes. According to the estimation results the four different IPCC scenarios, i.e. A1F1, A2, B1 and B2, are associated to different welfare impacts. First, these reveal to depend on both the nature of the forest ecosystem service. For example, cultural values reveal to be more sensitive to the four IPCC scenarios than the other ones, with the wood forest products being more resilient to climate change. Second, the distributional impacts of climate change on the provision of these goods and services do also depend on the geo-climatic regions under consideration. For the Scandinavian group of countries, B1 is ranked with the highest level of provision of carbon sequestration services, amounting to 46.3 billion dollars. In addition, we can see that cultural services provided by forest ecosystems have their highest levels in the Mediterranean countries, ranging from 8.4 to 9.0 million dollars, respectively in the B2 and B1 scenarios. Finally, we can see that the total value of wood forest products ranges between 41.2 and 47.5 million dollars for Central Europe to 5.4 and 7.2 million dollars in Northern Europe, respectively A1 and A2 scenarios. For this service, Mediterranean Europe provides a relatively weak role in the provision with values ranging from 6.4 million dollars in A1 scenario to 8.7 million dollars in the B2. In short, and to conclude, the valuation results (1) may contribute to a better understanding of the potential welfare loss in the context of climate change and the economic trade-offs between potential mitigation or adaptation strategies; and (2) confirm that climate change will be responsible for a re-distribution of welfare among the European countries, signalling the potential for a(n) agreement(s) among these same countries focus on the re-allocation of potential trade-offs among the countries.
Keywords: Q57; 330; Wood Products; Biodiversity; Climate Change; Market and Non-market Valuation Methods; Ecosystem Goods and Services; Millennium Ecosystem Assessment